MENGUBAH MINDSET KEPEMIMPINAN PENDIDIKAN: TELAAH PEMIKIRAN PENDIDIKAN DARI OTORITER KE DEMOKRASI - Siswadi, Siswadi (STKIP Pesisir Selatan, 2022)
This study aims to analyze the transformation of educational leadership mindset from an authoritarian model to a democratic one through a conceptual review of educational thought in the context of digital era transformation. This research employs a qualitative approach using a library research method, analyzing relevant scientific literature published between 2018 and 2021. The findings indicate that educational leadership has undergone a significant paradigm shift, from an authoritarian model characterized by hierarchical, rigid, and centralized power structures to a democratic leadership model that emphasizes participation, collaboration, and empowerment. This transformation is influenced by digital technological advancements, the evolution of leadership from Leadership 1.0 to Leadership 5.0, and the demands of 21st-century education. Furthermore, the digitalization of education presents challenges such as technological inequality, limited digital competencies, and issues related to ethics and data security, while also providing opportunities for more flexible, innovative, and inclusive learning. In this context, adaptive leadership becomes a key strategy in managing change through its roles as a change agent, innovation driver, and collaboration facilitator. Therefore, transforming the mindset of educational leadership from authoritarian to democratic is a strategic step toward developing a responsive, human-centered, and sustainable education system.